2009
DOI: 10.1208/s12249-009-9264-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclodextrin Complexation of Curcumin on its Solubility and Antiangiogenic and Anti-inflammatory Activity in Rat Colitis Model

Abstract: Abstract. The purpose of the study was to prepare and evaluate the anti-inflammatory activity of cyclodextrin (CD) complex of curcumin for the treatment of inflammatory bowel disease (IBD) in colitisinduced rat model. Inclusion complexes of curcumin were prepared by common solvent and kneading methods. These complexes were further evaluated for increase in solubility of poorly soluble curcumin. The inclusion complexes were characterized for enhancement in solubility, in vitro dissolution, surface morphology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(172 citation statements)
references
References 24 publications
14
156
0
2
Order By: Relevance
“…For example, structural modification or cyclodextrin complexation has been used as molecular strategies to enhance the oral bioavailability of curcumin. 35,36 Researchers have also investigated nanoscale formulations of curcumin, such as liposomes, microemulsions, and micelles, for potential therapeutic applications. [37][38][39][40][41][42] The nanoscale effect by which such drug delivery systems improve the oral performance of curcumin involves increasing the surface area and interactions of curcumin, thereby providing better water dispersibility to enhance its absorption.…”
Section: Resultsmentioning
confidence: 99%
“…For example, structural modification or cyclodextrin complexation has been used as molecular strategies to enhance the oral bioavailability of curcumin. 35,36 Researchers have also investigated nanoscale formulations of curcumin, such as liposomes, microemulsions, and micelles, for potential therapeutic applications. [37][38][39][40][41][42] The nanoscale effect by which such drug delivery systems improve the oral performance of curcumin involves increasing the surface area and interactions of curcumin, thereby providing better water dispersibility to enhance its absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The CU-PC-C and CU-HSPC-C have lower protein binding, with no signs of hemolysis, demonstrating their suitability for therapeutic application. In vivo studies of CU complexes have shown improved bioavailability and therefore are more effective systems for delivering CU into tumors (Maiti et al, 2007;Yadav et al, 2009). Phospholipids, the major components of the complexes that have good biocompatibility, could promote the delivery through the cell membrane and enhance drug concentration in the cells, further enhancing the anti-cell effect of the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…From the in vitro release study, it was evident that the release of CU from complexes was sustained and endured for a longer period of time as compared to plain CU (Figure 3). Release of CU was almost completed within 6 h, whereas it was evident that both complexes (CU-PC-C and CU-HSPC-C) exhibited faster dissolution rates (67.45% and 49.43%, respectively) up to 24 h. The enhancement of dissolution rate obtained with inclusion complexes could also be due to CU wettability and formation of readily soluble complexes in the dissolution medium (Yadav et al, 2009). …”
Section: In Vitro Dissolution Studymentioning
confidence: 98%
See 1 more Smart Citation
“…However, around 2005, Razella Kurzrock's group at MD Anderson Cancer Center solubilized curcumin by encapsulating curcumin in liposomes, and successfully started demonstrating its high efficacy in suppressing the PAK1-dependent growth of human colon and pancreatic cancer xenografts in mice: Curcumin in liposomes (20-40 mg/kg) suppresses the growth of these cancers by 50% (35,36). Furthermore, in 2009 an Indian group led by Sarasija Suresh at Nootan Dental College in Bangalore found that a chemically synthesized beta-dextrin derivative called hydroxypropyl-beta-CD would be the best among CDs to solubilize curcumin effectively and showed both its antiangiogenic and anti-inflammatory effects in vivo (37). Thus, in the future (probably in a decade or so) curcumin in either liposomes or CDs would become available on the market for the therapy of these cancers and NF tumors as well.…”
Section: Curcumin (Turmeric)mentioning
confidence: 99%